Electronic Ecological Momentary Assessment (EMA) in youth with bipolar disorder: Demographic and clinical predictors of electronic EMA adherence. (September 2019) - Gershon, Anda; Kaufmann, Christopher N.; Torous, John; Depp, Colin; Ketter, Terence A.
Abstract: Background: Ecological momentary assessment (EMA) is increasingly used to characterize patients' daily lives, monitor mood, and test efficacy of treatment interventions. However, few studies have examined patient characteristics impacting adherence with EMA protocols, and to our knowledge, no such study has been conducted in youth with bipolar disorder (BD). Methods: As part of a larger observational study, 14- to 21-year-olds diagnosed with BD, and who were between episodes of illness ( n = 39, 19.0 ± 2.05 Mean ± Standard Deviation years old, 74.4% female) and psychiatrically healthy controls ( n = 47, 18.3 ± 2.40 years old, 66.0% female) completed baseline diagnostic and symptom severity interviews, and were instructed to complete diary assessments of mood, sleep, and behavior electronically three times per day for 21 consecutive days (i.e., in total 5418 (or 63 per person) diary entries). Multiple regression was used to examine effects of BD participants' demographic and clinical characteristics on diary completion rates. Results: 53.8 ± 9.3 diary entries per person were actually completed. Adherence rates were high (87.5% of healthy controls and 80.4% of adolescents with BD), but were still significantly poorer in youth with BD. Adequate adherence (≥80%) rates were also significantly poorer in youth with BD relative to healthy controls (56.4% versus 83.0%). Among youth with BD, more lifetime suicide attempts and higher current mood elevation symptom severity predicted significantly poorer adherence. Limitations: Limited sample size/generalizability. Conclusions: Findings highlight the importance of considering the impact of patient characteristics on adherence with EMA protocols among youth with severe mental illness. Highlights: Ecological momentary assessment (EMA) is an increasingly used research methodology. There are few EMA feasibility/adherence studies in youth with bipolar disorder (BD). Adherence with thrice-daily EMA was high but still poorer in BD youth versus controls. Greater illness severity was associated with poorer adherence in BD youth. Ensuring EMA studies are optimal for patient adherence may have far-reaching benefits.